Idea and Ontology : An Essay in Early Modern Metaphysics of Ideas - Hight, Marc A., 1969- (Book collections on Project MUSE., 2008)
"Provides an interpretation of the development of the ontology of ideas from Descartes to Hume that reaffirms the vital role metaphysical concerns played in early modern thinking"--Provided by publisher.